Velocity analysis of planar mechanisms based on conversion mechanism - LI Xiuming; WANG Changlu; DONG Zhifeng (Jixie chuandong)
ObjectiveIn the scenario where the dimensions of the mechanism and the motion law of the driving link are already known, the purpose of kinematic analysis of mechanisms is to determine the motion characteristics of other links within the mechanism and to address two types of problems: velocity analysis concerning two points on the same link and velocity analysis concerning coincident points between two links in a planar mechanism. However, the velocity analysis of coincident points between two links is relatively difficult to comprehend.MethodsBy utilizing the composition principle of planar mechanisms, the planar mechanism was disassembled into the driving link and fundamental link groups. A reverse motion was imposed on the links undergoing planar motion within the fundamental link groups, thereby resulting in mechanism transformation. The mechanism transformation velocity analysis method was employed to perform corresponding velocity analysis for the five types of class Ⅱ fundamental link groups, which was applicable to both aforementioned types of problems.ResultsThe accuracy of the mechanism transformation velocity analysis method is validated through practical examples.